2002
DOI: 10.1124/jpet.302.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin-Induced Renal Cell Apoptosis: Caspase 3-Dependent and -Independent Pathways

Abstract: The chemotherapeutic cisplatin causes renal dysfunction and renal proximal tubular cell (RPTC) apoptosis. The goal of these studies was to examine the role of p53, caspase 3, 8, and 9, and mitochondria in the signaling of cisplatin-induced apoptosis. Cisplatin (50 M) produced time-dependent apoptosis in RPTCs, causing cell shrinkage, a 50-fold increase in caspase 3 activity, a 4-fold increase in phosphatidylserine externalization, and 5-and 15-fold increases in chromatin condensation and DNA hypoploidy, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
215
1
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 330 publications
(252 citation statements)
references
References 34 publications
33
215
1
3
Order By: Relevance
“…Several studies including ours have previously demonstrated activation of executioner caspases (caspase-3/7 and -6) in both in vitro 12,13 and in vivo 14,15 models of cisplatin-induced AKI. Similarly, induction of p53 transcription factor was demonstrated in RTECs in both in vitro [16][17][18] and in vivo 19 studies of cisplatin AKI. Inhibiting the activation of p53 protein by pifithrin-a, a pharmacological inhibitor of p53, blocked caspase activation.…”
mentioning
confidence: 67%
See 1 more Smart Citation
“…Several studies including ours have previously demonstrated activation of executioner caspases (caspase-3/7 and -6) in both in vitro 12,13 and in vivo 14,15 models of cisplatin-induced AKI. Similarly, induction of p53 transcription factor was demonstrated in RTECs in both in vitro [16][17][18] and in vivo 19 studies of cisplatin AKI. Inhibiting the activation of p53 protein by pifithrin-a, a pharmacological inhibitor of p53, blocked caspase activation.…”
mentioning
confidence: 67%
“…Inhibiting the activation of p53 protein by pifithrin-a, a pharmacological inhibitor of p53, blocked caspase activation. [16][17][18] One of the mechanisms whereby p53 can control caspase activation is by direct transcriptional regulation of their expression. However, transcriptional control of caspases and the functional significance of this regulation are not known in renal injury.…”
mentioning
confidence: 99%
“…To evaluate whether Hsp70 siRNA can inhibit Hsp70 protein expression during treatment with cisplatin, MG63 cells were first transfected with Hsp70 siRNA for 48 h, following which they were treated with 50 μM cisplatin for 48 h. The dosage of cisplatin (50 μM) was selected as a high-dose administration example (Cummings et al 2002;Liu et al 2014b). The effect of Hsp70 siRNA transfection of MG63 cells on cisplatin induction of Hsp70 expression was then analyzed using Western blotting and real-time RT-PCR.…”
Section: Effects Of Hsp70 Sirna Transfection On Cisplatin Induction Omentioning
confidence: 99%
“…Cisplatin has been shown to induce apoptotic cell death in human cancer cells, including A431 cells (Gonzalez et al, 2001;Cummings and Schnellmann, 2002;Sawada et al, 2003). To investigate the mechanism by which Titanocene Y induces cell death, A431 cancer cells were stained with Annexin V and propidium iodide to detect early and late apoptotic cells.…”
Section: Titanocene Y Induces Apoptotic Cell Death In A431 Cellsmentioning
confidence: 99%